The Effect of Self-Management on Stress, Security and Job Satisfaction of MSMEs Entrepreneurs in Bandung City - Putri, Mediany Kriseka; Wahyuningsih, Usha Fatihah (Research Center and Case Clearing House PPM School of Management, 2025)
The Covid-19 pandemic that emerged since 2020 forced MSMEs in Bandung City to find survival strategies amid economic pressures and changes in work routines that trigger stress. This study aims to identify the role of three self-management training practices, excessive workload, and attention to detail in influencing entrepreneurial stress, sense of security, and job satisfaction. The study used a quantitative method with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique and involved 408 respondents of MSME actors in Bandung City. The results of the analysis showed that workload and attention to detail had a significant effect on stress, sense of security, and job satisfaction. Meanwhile, exercise did not have a significant effect on stress. These findings contribute to the understanding of the importance of self-management in dealing with work pressure in the MSME sector. The implications of this study can be used as evaluation material for MSME actors in managing workload, increasing focus on detail, and reviewing the effectiveness of physical activity as an effort to reduce stress.